Risk factors for 30-day mortality in patients with pneumonia who receive appropriate initial antibiotics: an observational cohort study. Issue 9 (September 2015) - Shindo, Yuichiro; Ito, Ryota; Kobayashi, Daisuke; Ando, Masahiko; Ichikawa, Motoshi; Goto, Yasuhiro; Fukui, Yasutaka; Iwaki, Mai; Okumura, Junya; Yamaguchi, Ikuo; Yagi, Tetsuya; Tanikawa, Yoshimasa; et al.
Summary: Background: Appropriate initial antibiotics are essential for the treatment of infectious diseases. However, some patients with pneumonia might develop adverse outcomes, despite receiving appropriate initial antibiotics. We aimed to clarify the risk factors for 30-day mortality in patients who received appropriate initial antibiotics and to identify potential candidates who would benefit from adjunctive therapy. Methods: From March 15, to Dec 22, 2010, we did a prospective, observational study at ten medical institutions in hospitalised patients (aged ≥20 years) with pneumonia. We did a multivariable logistic regression analysis to calculate odds ratios (ORs) and 95% CI to assess the risk factors for 30-day mortality. This study was registered with the University Medical Information Network in Japan, number UMIN000003306. Findings: The 30-day mortality was 11% (61 of 579 patients) in the appropriate initial antibiotic treatment group and 17% (29 of 168) in the inappropriate initial antibiotic treatment group. Albumin concentration of less than 30 mg/L (adjusted OR 3·39, 95% CI 1·83–6·28), non-ambulatory status (3·34, 1·84–6·05), pH of less than 7·35 (3·13, 1·52–6·42), respiration rate of at least 30 breaths per min (2·33, 1·28–4·24), and blood urea nitrogen of at least 7·14 mmol/L (2·20, 1·13–4·30) were independent risk factors in patients given appropriate initial antibiotic treatment. The 30-day mortality was 1% (one of 126 patients), 1% (two of 168), 17% (23 of 137), 22% (20 of 89), and 44% (14 of 32) for patients with no, one, two, three, and four or five risk factors, respectively. Interpretation: Patients with two or more risk factors were at a higher risk of death during the 30 days assessed than were individuals with no or one risk factor, despite appropriate initial antibiotic treatment. Therefore, adjunctive therapy might be important for improving outcomes in patients with two or more risk factors. Funding: Central Japan Lung Study Group.